The Effect of Pandemic Covid-19 on Discontinuation of Work Relationship with Management Policy as a Moderating Variables - Muhammad Sapruwan; Wahyu Aji Pangestu (Journal of Research in Business, Economics, and Education, 2022)
The purpose of this study is to examine the existence of company management policies that can strengthen the influence of the COVID-19 pandemic on termination of employment. The population sample in this study was 82 respondents. The analytical method used is moderating regression analysis. The results of this research study are that the company's management policies significantly strengthen the influence of the COVID-19 pandemic on termination of employment. The implication of this study is that companies must be careful during the COVID-19 pandemic in issuing policies because they can encourage bankruptcy, for that they must have strategies: Expanding market share; alternative substitute products; selective procurement of product materials; delay in asset procurement; reduce management allowances; eliminating overtime; selection and maintain optimal health of the workforce.